Multi-Response Desirability Optimisation of Sucrose Charge in Black-Tea Kombucha: Ethanol, Acetic Acid, and Biocellulose as Critical Quality Attributes - Eki Noor Istiqomah; Sri Hartati Yuliani (HM Publisher, 2026)
Kombucha is a functional beverage produced by a symbiotic consortium of acetic acid bacteria and osmotolerant yeasts, and its commercial acceptability depends on a narrow compliance window in which residual ethanol must remain below 0.50% w/v while organic acidity is sufficient for flavour and microbial safety. The initial sucrose charge is the single manipulable process parameter that governs both outcomes, yet it is rarely treated as a formally optimised critical process parameter. Four sucrose charges (5, 10, 15 and 20% w/v) were evaluated in black-tea kombucha fermented statically for 14 days at 25–28 °C with a standardised 50 g pellicle and 10% v/v starter, three vessels per level. Composites were assayed in analytical triplicate by GC-FID (ethanol), ion-exclusion HPLC (acetic acid), potentiometry (pH) and alkalimetry (titratable acidity), with calliper measurement of pellicle thickness. Data were analysed by one-way ANOVA with Shapiro–Wilk, Levene and lack-of-fit diagnostics, Tukey's HSD, polynomial response modelling and Derringer–Suich desirability optimisation. Sucrose charge affected every attribute (all p < 0.001; η² = 0.685–0.998). Ethanol was biphasic, peaking at 0.341 ± 0.007% w/v (95% CI 0.324–0.359) at 10% sucrose — only 68% of the compliance threshold — whereas acetic acid fell monotonically and the acetification index collapsed 9.9-fold from 5% to 20% sucrose. Pellicle thickness increased strictly linearly (R² = 0.974). Composite desirability identified 19.1% w/v as the predicted optimum within a 15–20% w/v design space, with 15% preferred when ethanol headroom is prioritised. Sucrose charge is a tractable, instrument-free control lever for halal-compliant kombucha manufacture.